PRIVACY CALCULUS IN THE ERA OF ZERO-PARTY DATA: HOW VALUE EXCHANGE FRAMING SHAPES WILLINGNESS TO DISCLOSE - Shinta Widyastati; Lukmanul Hakim; Tibrani (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This article explores the privacy calculus in the era of zero-party data, focusing on how value exchange framing influences consumers’ willingness to disclose personal information. As digital marketing shifts away from third-party tracking toward consent-based data practices, understanding the factors that drive voluntary data sharing has become increasingly important. Drawing on a narrative literature review, this study integrates insights from marketing, consumer behavior, and privacy research to examine how individuals evaluate the trade-off between perceived benefits and perceived risks. The findings highlight that value exchange framing—whether functional, emotional, or monetary—plays a critical role in shaping perceptions of value and influencing disclosure decisions. Functional and emotional framing tend to enhance perceived relevance and trust, while monetary incentives may produce mixed effects by raising concerns about data exploitation. The study also identifies key moderating factors, including privacy concerns, trust in brands, and data literacy, which influence how consumers interpret value propositions. A conceptual framework is proposed to illustrate the relationships between value framing, mediating perceptions, and disclosure outcomes. The article contributes to theory by extending privacy calculus in the context of zero-party data and offers practical insights for designing transparent and effective data-sharing strategies.